Etika Pergaulan Sosial Dalam Al-Qur’an (Studi Komparatif Tafsir Al-Azhar Dan Tafsir Al-Miṣbah Dalam Surah Al-Qashas Ayat 23-28) - Mohammad Fattah; Zaffan Haidar (CV. ITTC INDONESIA, 2025)
The Qur’an teaches ethical values in social life, including in Surah Al-Qashash verses 23-28, which narrates the encounter between Prophet Musa (AS) and two women in Madyan. This story contains moral values such as social care, etiquette in interactions, as well as trustworthiness and responsibility. This study compares the interpretations of M. Quraish Shihab in Tafsir al-Misbah and Buya Hamka in Tafsir al-Azhar to understand how both scholars interpret social ethics in these verses. This research employs a qualitative method with a library research approach. Data was collected through document studies of tafsir books and related literature, then analyzed using interpretation, description, and comparative methods. The findings indicate that both scholars emphasize the importance of social ethics, particularly in maintaining politeness and modesty. M. Quraish Shihab focuses more on linguistic aspects and the relevance of the verses in a modern social context, whereas Buya Hamka emphasizes the spiritual aspect and the exemplary character of Prophet Musa in facing life’s challenges. Tafsir al-Misbah is more academic and systematic, while Tafsir al-Azhar is more reflective and easier to understand for the general public. Despite their different approaches, both tafsir emphasize that the ethical values in these verses are essential for social life.